A precise targeting of Staphylococcus aureus with phage RBP-decorated antibiotic-loaded nanoparticles - Dokuz, Senanur; Coksu, Irem; Acar, Serap; Ozbek, Tulin (WILEY-V C H VERLAG GMBH, 2025)
Resistant strains of Staphylococcus aureus, which have emerged due to the excessive and indiscriminate use of antibiotics, have become one of the most significant causes of hospital-acquired infections, highlighting the necessity for specific and effective alternative methods in combating them. Leveraging the therapeutic potential of bacteriophage receptor binding protein (RBP), which occurs unique and irreversible binding of its host, in recognizing bacteria renders them valuable components in the development of targeted nanoparticle-based drug delivery systems, and offers promising approach to combat antibiotic resistance. In this study, synthesis and characterization of rifampicin-loaded PLGA nanoparticle (RIF-NP) were conducted and for selective targeting of S. aureus, rGp144, the RBP derived from Bacteriophage K, was conjugated onto the surface of the synthesized RIF-NP (RIF144-NP). While RIF-NP initially exhibited approximately a zeta potential of -26 mV and a size of 250 nm, after the conjugation with rGp144 led to an increase in zeta potential to -11 mV and a size to 300 nm. FT-IR analysis after conjugation confirmed the presence of primary amide bands in the regions of 1650 cm-1 and 1550 cm-1. Furthermore, the nanoparticles exhibited an encapsulation efficiency of 35.26% and a drug loading capacity of 26.64%. When the antimicrobial activities were evaluated, it was observed that compared to free RIF, the nano systems reduced the MIC value by twofold for all S. aureus strains. Incorporating a targeting strategy based on phage RBP in decoration to the surface of nanoparticular drug carriers represents a noteworthy and innovative treatment when combating bacterial infections.
Keywords: antibiotic targeting; phage receptor binding protein; PLGA nanoparticle; rifampicin; S. aureus infections; ANTIBACTERIAL ACTIVITY; PLGA NANOPARTICLES; MECHANISMS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology